2019
DOI: 10.1016/j.neuint.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of the neuroprotective activities of astaxanthin and fucoxanthin against amyloid beta (Aβ1-42) toxicity and aggregation

Abstract: Amyloid beta (Aβ) can aggregate and form plaques, which are considered as one of the major hallmarks of Alzheimer's disease. This study aims to directly compare the neuroprotective activities in vitro of two marine-derived carotenoids astaxanthin and fucoxanthin that have shown a spectrum of biological activities, including neuroprotection. The in vitro neuroprotective activities were investigated against Aβ 1-42-mediated toxicity in pheochromocytoma (PC-12) neuronal cells using the MTT cell viability assay, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 55 publications
0
62
0
1
Order By: Relevance
“…Several metabolites of marine algae have shown anti-amyloidogenic potentials ( Table 1 ). For example, fucoxanthin at variant concentrations reduced the formation of Aβ 1–42 fibril and Aβ1–42 oligomers, when co-incubated with Aβ 1–42 monomers [ 135 , 136 ]. Both studies also demonstrated that fucoxanthin has been shown to inhibit Aβ aggregation [ 135 , 136 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…Several metabolites of marine algae have shown anti-amyloidogenic potentials ( Table 1 ). For example, fucoxanthin at variant concentrations reduced the formation of Aβ 1–42 fibril and Aβ1–42 oligomers, when co-incubated with Aβ 1–42 monomers [ 135 , 136 ]. Both studies also demonstrated that fucoxanthin has been shown to inhibit Aβ aggregation [ 135 , 136 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…For example, fucoxanthin at variant concentrations reduced the formation of Aβ 1–42 fibril and Aβ1–42 oligomers, when co-incubated with Aβ 1–42 monomers [ 135 , 136 ]. Both studies also demonstrated that fucoxanthin has been shown to inhibit Aβ aggregation [ 135 , 136 ]. Inhibition of β-site amyloid precursor protein cleaving enzyme 1 (BACE1) with fucoxanthin was of a mixed-type [ 134 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…These findings are of particular interest, as beneficial effects of LXR agonists on cognition are not necessarily accompanied by a reduced Aβ plaque load 14,41 . Recently, it has been reported that other constituents of Sargassum fusiforme, such as fucosterol, fucoidan, and fucoxantin improve learning and memory deficiencies in pharmacological models for cognitive impairment [61][62][63] . Although synergism among constituents of Sargassum fusiforme is likely, future studies should determine whether 24(S)-Saringosterol is sufficient to improve cognitive performance and AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the protection of neural cells against oxidative damage may be a potential strategy to treat AD. Several in vitro or in vivo studies have explored the function of antioxidant and antiapoptotic drugs in ameliorating AD [4][5][6] but the approach is time-consuming and costly, plus the safety concern, which limits the use of these drugs in AD treatment. Moreover, the blood-brain barrier (BBB) dampens the efficacy of these drugs, since over 98% of small molecule drugs and *100% of large molecule drugs can not pass the BBB [7].…”
Section: Introductionmentioning
confidence: 99%